KAJIAN BENTUK, MAKNA UKIRAN MINANGKABAU DAN MAKNA PENEMPATAN KALIGRAFI ARAB PADA FASADE MASJID RAYA PROVINSI SUMATERA - SYLVA RAHMAWATI, Drs. Efrizal, M.Pd, Drs. Syafei,M.Ag (Serupa The Journal of Art Education, 2014)
The Greatest Mosque in West Sumatera has façade on the roof, it has carved object with high art quality by mixing traditional art from West Sumatera (Minangkabau) and Arabic culture, it mixing traditional carved from Minangkabau and calligraphy.Now days in the modern era Minangkabau people did not have any responsibility to their inheritance culture. We can see that from the habitually of Minangkabau people they did not want to learn about the meaning from their old tradition including the carved at that mosque. This condition must be anxiousness for Minangkabau people without awareness their own tradition, their own culture will beextinct. So the purposes of this research are to describe: shape,utility and meaning from that façade on the roof of The Greatest Mosque in West SumateraKeywords: Kajian Bentuk, Makna Ukiran Minangkabau dan Makna Penempatan Kaligrafi Arab Pada Fasade Masjid Raya Provinsi Sumatera